Antiretroviral therapy use during pregnancy and adverse birth outcomes in South African women - Malaba, Thokozile Rosemary (Department of Public Health and Family Medicine, 2017)
Background Studies suggest antiretroviral therapy (ART) use during pregnancy may be associated with adverse pregnancy outcomes. Given the large numbers of pregnancies exposed to ART, better understandings of potential associations with commonly used ART regimens and adverse pregnancy outcomes is critical. With the number of women on ART initiated before conception rapidly increasing, understanding how current recommended regimens and timing of ART initiation may influence pregnancy outcomes is critically important. Methods This mini-dissertation presents a research protocol (Section A), literature view (Section B) and journalformatted manuscript (Section C) for a study of ART use and birth outcomes among HIV-infected women and a comparator cohort of HIV-uninfected women. Pregnant women seeking care at the Gugulethu MOU, a primary-level antenatal care facility in Cape Town, South Africa were enrolled between March 2013 and August 2015. Pregnancy dating was based on research ultrasound, or last menstrual period/clinical exam where ultrasound was unavailable. Women were followed from their 1st antenatal visit through delivery. Analyses compared birth outcomes (preterm (PTD), low birthweight (LBW) and small for gestational age (SGA) deliveries) between HIV-infected and uninfected women; and between women on ART initiated before conception versus those initiating ART during pregnancy. Results In 1554 women with live singleton births (mean birthweight, 3079g; 21% preterm; 13% LBW; 12% SGA), a higher prevalence of PTD (22% vs 13%, p=0.001) and LBW (14% vs 9%, p=0.030) were observed in the HIV-infected compared to HIV-uninfected women. Adverse birth outcomes (PTD, LBW and SGA) did not vary systematically among the HIV-infected women regardless of ART initiation timing (initiated ART before conception or initiated ART to during pregnancy). The absence of associations between the adverse birth outcomes and timing of ART initiation persisted after adjusting for maternal age, parity, height, CD4 cell count and viral load at 1st visit. Conclusions Levels of adverse birth outcomes, in particular PTD, remain high among HIV-infected women, however our findings from a routine care cohort demonstrate that the timing of initiation of widely used regimens before conception or during pregnancy do not appear to be associated with an increased risk in adverse pregnancy outcomes.